Isolation of Stigmasterol-3-O-β-D-arabinopyranosyl[1→4]-O-β-D-glucopyranoside from Seeds of Embelia ribes Burm. - Shukla, Mrityunjai (Asian Journal of Chemistry, 2011)
Embelia ribes Burm. which belongs to natural order myrsinacae, is commonly known as Baberang in Hindi. It is an evergreen tree found throughout in India. Its fruit is hot and dry, with a sharp bitter taste, good appetizer, carminative, anthelmintic, alexiteric, laxative, alternative. It is reported to cure tumour ascites, bronchitis, mental diseases and its seeds possesses antiinflammatory and anthelmintic properties. The present work deals with the isolation and identification of the saponin MS-IV characterized as; stigmasterol-3-O-β-Darabinopyranosyl[ 1→4]-O-β-D-glucopyranoside from the seeds of Embelia ribes Burm.